2022
DOI: 10.1111/bph.15790
|View full text |Cite
|
Sign up to set email alerts
|

Peptide fragments of bradykinin show unexpected biological activity not mediated by B1 or B2 receptors

Abstract: Background and Purpose Bradykinin (BK‐(1–9)) is an endogenous nonapeptide involved in multiple physiological and pathological processes. Peptide fragments of bradykinin are believed to be biologically inactive. We have now tested the two major peptide fragments of bradykinin in human and animals. Experimental Approach BK peptides were quantified by MS in male rats. NO release was quantified from human, mouse and rat cells loaded with DAF‐FM. Rat aortic rings were used to measure vascular reactivity. Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…The concentration-response curve supports BK fragments' role in stim-ulating NO generation. These in vitro findings collectively indicate that the examined BK segments were biologically active in promoting NO generation and that these actions were almost certainly triggered by signal transduction (Singh, 2020;Silva et al, 2022). The majority of the in vivo cardiovascular impacts of kinins, involving endothelium-dependent vasodilatation, smooth muscle contraction in the lungs and blood vessels, and enhanced vascular permeability, seem to be mediated by the B2 receptor ( Jean, et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The concentration-response curve supports BK fragments' role in stim-ulating NO generation. These in vitro findings collectively indicate that the examined BK segments were biologically active in promoting NO generation and that these actions were almost certainly triggered by signal transduction (Singh, 2020;Silva et al, 2022). The majority of the in vivo cardiovascular impacts of kinins, involving endothelium-dependent vasodilatation, smooth muscle contraction in the lungs and blood vessels, and enhanced vascular permeability, seem to be mediated by the B2 receptor ( Jean, et al, 2016).…”
Section: Discussionmentioning
confidence: 69%
“…The role of the BK in the regulation of coronary blood flow and its effects on heart disorders have been the subject of several experimental studies utilizing animal models. Local cardiac KKS is thought to play a key protective effect on the heart by postponing the onset of heart failure in conditions like myocardial infarction (Silva et al, 2022). Kallikrein gene transfer, tissue kallikrein infusion, human kallikrein overexpressing animals, B1 or B2 BK receptor knockout mice, and other techniques have all been used.…”
Section: Advances Inmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the expression of ACE1, which cleaves bradykinin into the metabolites bradykinin1-7 but not bradykinin1-5, as shown recently (Souza-Silva et al, 2022), is higher in severe COVID-19 patients (Akbari et al, 2022), representing one way by which bradykinin level is decreased in the plasma of SARS-CoV-2 infected individuals in comparison with the control group. Therefore, evaluating bradykinin1-7 and bradykinin1-5 would be of great importance to better elucidate the kinin pathways in COVID-19 pathology, as suggested by Souza-Silva et al (2022). Additionally, it was recently reported that carboxypeptidase N subunit 1, which cleaves bradykinin into des-Arg 9 -BK, is overexpressed in COVID-19 patients (Alfaro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The method employed to quantify the kinin peptides was similar to the one used by Souza-Silva et al (2022) . The liquid chromatography-tandem mass spectrometry instrument consisted of an ACQUITY I-class UPLC system (Waters, Milford, MA, United States) and Xevo TQ-S triple quadruple mass spectrometer (Waters, Milford, MA, United States of America).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation